The activity of native Bacillus subtilis strains in control of green mould disease of oyster mushroom (Pleurotus spp.) - Potočnik, Ivana; Milijašević-Marčić, Svetlana; Stanojević, Olja; Berić, Tanja; Stanković, Slaviša; Kredics, László; Hatvani, Lóránt (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2019)
The study aimed to isolate potential biocontrol agents from mushroom substrate that could serve as an alternative to toxic chemicals commonly used for disease control in mushroom production. The antagonistic potential of ten native Bacillus subtilis strains against the causal agents of green mould disease of oyster mushroom, Trichoderma pleuroti and Trichoderma pleuroticola, was evaluated. The antagonistic potential of Bacillus spp. strains was quantified in vitro based on dual cultivation with the pathogen. Growth inhibition of T. pleuroti ranged from 54.44% to 62.22% and no significant differences in antagonistic activity were found between the tested B. subtilis strains. Inhibition of T. pleuroticola was slightly higher, ranging from 55.56% to 69.62% and B. subtilis strain B-358 induced the highest growth inhibition. This research confirmed mushroom substrate to be a good source of antagonistic microorganisms with potentials for use in biological control of green mould in oyster mushroom production.